Late‐onset Pneumocystis jirovecii pneumonia in solid organ transplant recipients. Issue 2 (24th January 2014) - Perez‐Ordoño, L.; Hoyo, I.; Sanclemente, G.; Ricart, M.J.; Cofan, F.; Perez‐Villa, F.; de la, J. Puig; Moreno, A.; Cervera, C.
Abstract Anti‐Pneumocystis prophylaxis is recommended for at least 6–12 months after solid organ transplantation, as most cases of Pneumocystis jirovecii pneumonia (PCP) occur during the first year post transplantation. Herein, we report 4 cases of late‐onset PCP (>1 year post transplant). PCP appeared in a range of 50–68 months post transplant. Two cases had history of humoral rejection episodes treated with rituximab, and the other 2 had low CD4+ T‐cell count (<200 cells/mm3) at the time of diagnosis. All 4 patients survived. In conclusion, although the number of cases is low, we must be aware of the possibility of late‐onset PCP in solid organ transplant patients. The role of previous use of rituximab or persistent CD4+ T‐cell lymphopenia should be addressed in future studies.